How molecular advances may improve the diagnosis and management of PTCL patients - Drieux, Fanny; Lemonnier, François; Gaulard, Philippe (Frontiers in Oncology, 2023)
Peripheral T-cell lymphomas (PTCL) comprised more than 30 rare heterogeneous entities, representing 10 to 15% of adult non-Hodgkin lymphomas. Although their diagnosis is still mainly based on clinical, pathological, and phenotypic features, molecular studies have allowed for a better understanding of the oncogenic mechanisms involved and the refinement of many PTCL entities in the recently updated classifications. The prognosis remains poor for most entities (5-year overall survival < 30%), with current conventional therapies based on anthracyclin-based polychemotherapy regimen, despite many years of clinical trials. The recent use of new targeted therapies appears to be promising for relapsed/refractory patients, such as demethylating agents in T-follicular helper (TFH) PTCL. However further studies are needed to evaluate the proper combination of these drugs in the setting of front-line therapy. In this review, we will summarize the oncogenic events for the main PTCL entities and report the molecular targets that have led to the development of new therapies. We will also discuss the development of innovative high throughput technologies that aid the routine workflow for the histopathological diagnosis and management of PTCL patients.